A new method for early detection of mass concern about public health issues. Issue 4 (3rd April 2017) - Pei, Jiayin; Yu, Guang; Tian, Xianyun; Donnelley, Maureen Renee
Abstract : During a public health crisis, risk communication professionals and other risk managers need timely and reliable information about the public reaction as soon as possible in order to effectively carry out their responsibilities. Based on a data-set of microblog news posts, this article presents a method that can forecast to what extent news about a public health issue will be disseminated. The study makes advances in rapidly tracking citizens' reaction towards public health issues by monitoring news media on microblog sites. The findings show that the proposed method can detect early on the intensity of social reaction on a public health issue as well as provide alert signals. The method can also complement existing risk detection systems and help in the design of other powerful risk analytics tools.